The "lost" Dialogue of Gregory the Great: the life of St. Scholastica - Posa, Carmel (Liturgical Press, 2024)
"In The Lost Dialogue of Gregory the Great, Carmel Posa, SGS, applies a "disciplined imagination" and the ancient hagiographical method to recover the missing life and voice of St. Scholastica of Nursia. Drawing on a wide range of scholarship, including Gregory the Great's four famous dialogues, biblical models, and the Rule of Benedict, Posa follows a technique similarly used by Saint Gregory himself to create an account of Scholastica's life"--